- #26

- 466

- 0

So

c= log (2r+4) - r

So

log u = x

c= log (2r+4) - r

^{2}/3So

log u = x

^{2}/3 + log (2r+4) - r^{2}/3You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter andrey21
- Start date

- #26

- 466

- 0

So

c= log (2r+4) - r^{2}/3

So

log u = x^{2}/3 + log (2r+4) - r^{2}/3

c= log (2r+4) - r

So

log u = x

- #27

hunt_mat

Homework Helper

- 1,745

- 26

- #28

- 466

- 0

So:

t = x^{2} /3 - r^{2} /3

r^{2} /3 = x^{2} /3-t

r^{2} = x^{2} -3t

r = SQRT (x^{2} -3t)

t = x

r

r

r = SQRT (x

- #29

hunt_mat

Homework Helper

- 1,745

- 26

- #30

- 466

- 0

So :

r = [itex]\pm[/itex]SQRT (x^{2} -3t)

What is the next step?

r = [itex]\pm[/itex]SQRT (x

What is the next step?

- #31

hunt_mat

Homework Helper

- 1,745

- 26

- #32

- 466

- 0

Which equation shall I plug the r value into?

Is it:

log u = x^{2}/3 + log (2r+4) - r^{2}/3

Is it:

log u = x

- #33

hunt_mat

Homework Helper

- 1,745

- 26

Yes.

Share: